2019
DOI: 10.1038/s41598-019-49116-x
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox code model of heterodont tooth in mammals revised

Abstract: Heterodonty is one of the hallmarks of mammals. It has been suggested that, homeobox genes, differentially expressed in the ectomesenchyme of the jaw primordium along the distal-proximal axis, would determine the tooth classes (homeobox code model) based on mouse studies. Because mouse has highly specialized tooth pattern lacking canine and premolars (dental formula: 1003/1003, for upper and lower jaws, respectively), it is unclear if the suggested model could be applied for mammals with all tooth classes, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…The underlying hypothesis is based on the fact that Fgf10 is upregulated in the branchial mesoderm by Fgf3 and Fgf8 (Alvarez et al, 2003;Wright and Mansour, 2003;Wright et al, 2004;Ladher et al, 2005;Aggarwal et al, 2006). FGF signaling in turn causes an upregulation of Msx1 in the branchial mesoderm during exactly the developmental period we are looking for (Wakamatsu et al, 2019; one embryonic day later: Chen et al, 1996). Exposure of our embryos to 0.5 µM of the pan-FGFR inhibitor PD173074 already leads to a discrete attenuation of the Msx1/2 signal (Supplementary Figure 2).…”
Section: Methodological Considerationsmentioning
confidence: 97%
“…The underlying hypothesis is based on the fact that Fgf10 is upregulated in the branchial mesoderm by Fgf3 and Fgf8 (Alvarez et al, 2003;Wright and Mansour, 2003;Wright et al, 2004;Ladher et al, 2005;Aggarwal et al, 2006). FGF signaling in turn causes an upregulation of Msx1 in the branchial mesoderm during exactly the developmental period we are looking for (Wakamatsu et al, 2019; one embryonic day later: Chen et al, 1996). Exposure of our embryos to 0.5 µM of the pan-FGFR inhibitor PD173074 already leads to a discrete attenuation of the Msx1/2 signal (Supplementary Figure 2).…”
Section: Methodological Considerationsmentioning
confidence: 97%
“…Previous studies of heterodont mammals including the house shrew ( S. murinus ) and the ferret ( M. furo ), as well as a marsupial, the short‐tailed opossum ( Monodelphis domestica ), demonstrated conservation of the homeobox code among placental mammals and marsupials and extended the homeobox code to include canine and premolar teeth. These studies showed that distinct combinatorial expression domains of Barx1, Msx1 , and Alx3 distinguish the incisor, canine, and premolar regions from one another (Miletich et al, 2011; Wakamatsu et al, 2019; Yamanaka et al, 2015). In addition to specifying regions within the dentition, expression of Barx1 in the least shrew ( C. parva) has been shown to correlate positively with the number of cusps on premolar and molar teeth; teeth with more cusps have higher Barx1 expression (Miletich et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Homeobox genes play critical roles in patterning the dentition into distinct regions in which different tooth classes form, known as the homeobox code (McCollum & Sharpe, 2001; Sharpe, 1995). Initially studied in incisors and molars of mice, the homeobox code has been extended to canine and premolar teeth in shrews ( Suncus murinus, Cryptotis parva ) and ferrets ( Mustela furo ) (Miletich et al, 2011; Wakamatsu et al, 2019; Yamanaka et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, developmental studies, largely based on morphological observations of the dental lamina of species 29 including the ferret 30 , shrew 31,32 , straw-colored fruit bat 33 , opossum ( 34 and personal observations), and this study reveal that lower premolars and molars tend to develop in opposite directions, and thereby support the hypothesis that premolars and molars are patterned through independent mechanisms. From a molecular perspective, some evidence suggests that the early patterning of the jaw is driven by a "homeobox-code" that divides the jaw into territories that determine tooth classes prior to bud development (reviewed in [35][36][37] ). While these results suggest that tooth class specification and/or determination might occur prior to placode induction, results of other studies suggest that this early code is not sufficient to establish tooth class identity.…”
Section: Discussionmentioning
confidence: 99%